IoT characterisation and emulation system for electric water heaters - Fortuin, Liza (Stellenbosch : Stellenbosch University, 2025)
Fortuin, L. 2025. IoT Characterisation and Emulation system for Electric Water Heaters. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/5daf430e-7c7a-4434-af3c-623941d8602d